J. Hidalgo. You survive Teletransportation / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
Suppose that it was possible to teletransport. The teletransporter would destroy your old brain and body and construct an identical brain and body at a new location. Would you survive teletransportation? Many people think that teletransportation would kill you. On their view, the person that emerges from the teletransporter would be a replica of you, but it wouldn’t be you. In contrast, I argue that there’s no relevant difference between teletransportation and ordinary survival. So, if you survive ordinary life, then you survive teletransportation. Yet my argument may also show that we have little prudential reason to care about our survival in general.